Social Support for Psychology Masters Students Who Live Away from Home: A Case Study - Monica, Rezi; Abidin, Zainal; Lubis, Fitriani Yustikasari; Novita, Shally (Psyche 165 Journal, 2025)
First-year master's students in psychology face a transitional period with various challenges, including academic demands, social adjustments, and adaptation to a new environment, particularly for those living away from home for the first time. This study aims to describe participants' experiences and interpretations of social support during this period. A qualitative approach with a case study design was employed to explore the issue in depth. Data were collected through semi-structured interviews based on the theory of social support. The participants consisted of four first-year Master of Psychology students at Padjadjaran University, aged 18–25 years, who recently moved from their hometowns outside Java Island after completing their undergraduate studies, and were living independently in rented accommodations. The findings revealed that participants received and interpreted various forms of social support both on and off campus. Tangible support from friends, such as transportation assistance or companionship when sick, provided relief and convenience. Having support from parents and close friends, either in person or virtually, creates a sense of comfort and acceptance. Friendship groups also played a role in fostering social inclusion. Self-esteem support from parents, expressed through pride in the participants' achievements, enhanced their sense of worth. Appraisal support, including guidance and advice from parents, helps participants navigate challenges during their studies. Overall, these forms of social support played a crucial role in helping participants manage academic and personal challenges, contributing significantly to their adaptation and well-being as master's students living away from home.